Potassium ion battery negative electrode material and preparation method thereof
By using nickel-based dichalide material as the negative electrode material of potassium ion battery, the problem of structural collapse and low Coulomb efficiency of potassium ion battery during charging and discharging is solved, and faster charge and discharge rates and higher Coulomb efficiency are achieved.
Patent Information
- Application Number
- CN202411932819.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The problem of structural collapse and low Coulomb efficiency during the charging and discharge process of potassium ion battery negative electrode materials.
Nickel-based dichalide material is used as the negative electrode material of potassium ion battery. The material structure is nanoparticle, contains a carbon framework, and forms NiSTe or NiSeTe through heat treatment.
It improves the migration ability of potassium ions, enhances the charging and discharge rate and power density of the battery, and improves the efficiency of the Coulomb.
Smart Images

Figure CN119674060A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of potassium ion batteries, and in particular to the technical field of negative electrode materials for potassium ion batteries. Background Art
[0002] Sodium (Na) and potassium (K) are alkali metal elements like lithium, have similar chemical properties, and are abundant in the earth's crust. As energy demand continues to grow, the performance of traditional lithium-ion batteries is gradually stretched, and researchers have begun to explore the potential of sodium-ion batteries and potassium-ion batteries as alternatives to lithium-ion batteries.
[0003] However, compared to sodium ions and lithium ion The ionic radius of potassium ion is larger than that of This characteristic may cause structural collapse of the electrode during the charge and discharge process, which greatly limits the choice of negative electrode materials; in addition, existing potassium ion negative electrode materials also have the problem of low Coulomb efficiency. Summary of the invention
[0004] In view of this, the embodiments of the present disclosure provide a potassium ion battery negative electrode material and a preparation method, which at least partially solve the problems existing in the prior art.
[0005] In a first aspect, the embodiments of the present disclosure provide a negative electrode material for a potassium ion battery;
[0006] The negative electrode material is a nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe.
[0007] Optionally, the particle size of the nanoparticles is 100nm-600nm;
[0008] Optionally, the nickel-based disulfide material is based on a carbon material, and the carbon material structure includes one or more of a nanotube, a nanowire, a nanosheet, and a porous structure.
[0009] The carbon content of the nickel-based dichalcogenide material is 20%-80%.
[0010] In a second aspect, the present disclosure provides a method for preparing the nickel-based disulfide material of the first aspect, the method comprising:
[0011] Grinding the carbon source and the nickel source uniformly in a first mortar to obtain a mixture A;
[0012] Grind the sulfur source, one of the selenium source, and the tellurium source uniformly in a second mortar to obtain a mixture B;
[0013] Adding mixture A to mixture B and stirring evenly to obtain mixture C;
[0014] The mixture C is placed in a heat treatment device for heat treatment to obtain the nickel-based disulfide material. The structure of the nickel-based disulfide material is in the form of nanoparticles. The nickel-based disulfide is one of NiSTe and NiSeTe.
[0015] Optionally, the carbon source includes one or more of carbon cloth, carbon nanotubes, carbon nanowires, polyacrylonitrile, graphite, and graphene;
[0016] The nickel source includes one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel oxalate, and nickel nitrate hexahydrate;
[0017] The sulfur source includes one or more of thioacetamide, carbon disulfide, sulfur, and thiourea;
[0018] The selenium source includes selenium powder;
[0019] The tellurium source includes tellurium powder.
[0020] Optionally, the molar ratio of nickel source:carbon source is between 4:1 and 1:9;
[0021] The molar ratio of the mixture of the sulfur source and the tellurium source, or the mixture of the selenium source and the tellurium source, to the nickel source is 2:1.
[0022] Optionally, the heat treatment device includes a tubular furnace.
[0023] Optionally, the heating treatment includes:
[0024] Keep at 800-1000℃ for 30-180 minutes.
[0025] In a third aspect, the present disclosure provides a negative electrode plate for a potassium ion battery, wherein the material of the negative electrode plate is the nickel-based disulfide material described in the first aspect and the second aspect.
[0026] In a fourth aspect, the present disclosure provides a potassium ion battery, comprising the negative electrode sheet described in the third aspect.
[0027] The present disclosure discloses a negative electrode material for a potassium ion battery, wherein the negative electrode material is a nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe. Thus, by introducing double anions (S and Te, or Se and Te), the migration ability of potassium ions in the electrode material during the battery charging and discharging process can be improved. In other words, potassium ions can be extracted and embedded from the negative electrode faster, thereby improving the battery's charge and discharge rate and power density, as well as improving the coulombic efficiency.
[0028] In order to make the above-mentioned objectives, features and advantages of the present disclosure more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the following is a brief introduction to the drawings required for use in the embodiments. The drawings herein are incorporated into the specification and constitute a part of the specification. These drawings illustrate embodiments consistent with the present disclosure and are used together with the specification to illustrate the technical solutions of the present disclosure. It should be understood that the following drawings only illustrate certain embodiments of the present disclosure and should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can also be obtained based on these drawings without creative work.
[0030] Figure 1 is a SEM image of the sample of Example 1 provided in the embodiments of the present disclosure;
[0031] Figure 2 is a potassium ion diffusion barrier curve of NiSeTe provided in an embodiment of the present disclosure;
[0032] Figure 3 This is the charge and discharge image of the sample of Example 1 of the present invention;
[0033] Figure 4 Schematic diagram of the method for preparing nickel-based disulfide materials according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0034] The following describes the implementation methods of the embodiments of the present disclosure through specific specific examples. Those skilled in the art can easily understand other advantages and effects of the embodiments of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The embodiments of the present disclosure can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the embodiments of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the embodiments of the present disclosure.
[0035] In a first aspect, an embodiment of the present disclosure provides a negative electrode material for a potassium ion battery, wherein the negative electrode material is a nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe.
[0036] Among them, in the disclosed embodiments, ion diffusion refers to the ability of potassium ions to migrate in the electrode material during the battery charging and discharging process. Improving ion diffusion means that potassium ions can be extracted and embedded from the negative electrode faster, thereby improving the battery's charge and discharge rate and power density.
[0037] Specifically, since S, Se and Te atoms have different radius sizes, this difference allows S and Te, or the combination of Se and Te elements, to form double anion doping. This doping results in a large number of vacancies in the material, creating more channels for ion transport. At the same time, the micro-nanostructure of nickel-based dichalcogenide materials provides abundant active sites, which helps to reduce the transmission distance of ions and significantly improve the diffusion rate of ions.
[0038] Coulombic efficiency is a key indicator for evaluating the efficiency of electrical energy conversion during the charging and discharging process of a battery. Improving the coulombic efficiency can reduce the energy loss of the battery during the charging and discharging process, thereby improving the energy conversion efficiency. By optimizing the ion diffusion path, the transmission resistance of potassium ions in the electrode material can be reduced, and the side reactions caused by ion transport barriers can be reduced, which helps to improve the coulombic efficiency. In addition, high coulombic efficiency ensures that more electrical energy is effectively used in the insertion and deintercalation process of potassium ions, rather than being lost in the form of heat energy inside the battery, which further promotes the efficient transmission of ions.
[0039] The present disclosure discloses a negative electrode material for a potassium ion battery, wherein the negative electrode material is a nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe. Thus, by introducing double anions (S and Te, or Se and Te), the migration ability of potassium ions in the electrode material during the battery charging and discharging process can be improved. In other words, potassium ions can be extracted and embedded from the negative electrode faster, thereby improving the battery's charge and discharge rate and power density, as well as improving the coulombic efficiency.
[0040] The embodiment of the present disclosure provides a possible implementation method, the particle size of the nanoparticles is 100nm-600nm; the nickel-based disulfide material also includes a carbon skeleton; the carbon content of the nickel-based disulfide material is 20%-80%.
[0041] During the charge and discharge cycle of potassium ion batteries, negative electrode materials are often subjected to cyclic stress of volume expansion and contraction. This volume change may lead to damage to the material structure, thereby affecting the cycle life of the battery. However, nickel-based dichalcogenide materials composed of nanoparticles and carbon skeletons show excellent mechanical stability. The carbon skeleton not only provides the necessary space buffer for the volume change of nickel-based materials during the charge and discharge process, thereby reducing structural stress, but also enhances the electronic conductivity of the material.
[0042] In a second aspect, the present disclosure provides a method for preparing a nickel-based disulfide material, such as Figure 4 As shown, the method includes:
[0043] Step S101, grinding the carbon source and the nickel source in a first mortar to obtain a mixture A;
[0044] Step S102, grinding the sulfur source, the selenium source, and the tellurium source uniformly in a second mortar to obtain a mixture B;
[0045] Step S103, adding mixture A to mixture B and stirring evenly to obtain mixture C;
[0046] Step S104, placing the mixture C in a heat treatment device for heat treatment to obtain the nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe.
[0047] The first mortar and the second mortar may be different mortars or the same mortar.
[0048] Specifically, the carbon source includes one or more of carbon cloth, carbon nanotubes, carbon nanowires, polyacrylonitrile, graphite, and graphene; the nickel source includes one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel oxalate, and nickel nitrate hexahydrate; the sulfur source includes one or more of thioacetamide, carbon disulfide, sulfur, and thiourea; the selenium source includes selenium powder; and the tellurium source includes tellurium powder.
[0049] Specifically, the molar ratio of the nickel source:carbon source may be between 4:1 and 1:9; the molar ratio of the mixture of the sulfur source and the tellurium source, or the mixture of the selenium source and the tellurium source, to the nickel source may be 2:1.
[0050] Specifically, the heat treatment device includes a tubular furnace; the heating treatment includes: controlling the temperature of the tubular furnace at 800-1000° C. for 30-180 minutes to obtain the nickel-based disulfide material of the embodiment of the present disclosure.
[0051] By the method of the embodiment of the present disclosure, the structure of the obtained nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe. Thus, by introducing double anions (S and Te, or Se and Te), the migration ability of potassium ions in the electrode material during the battery charging and discharging process can be improved. In other words, potassium ions can be extracted and embedded from the negative electrode faster, thereby improving the battery's charge and discharge rate and power density, as well as improving the coulombic efficiency.
[0052] The embodiments of the present disclosure may use different combinations of carbon sources, nickel sources, sulfur sources and tellurium sources, or combinations of carbon sources, nickel sources, selenium sources and tellurium sources. Depending on the specific combination of carbon sources, nickel sources, sulfur sources and tellurium sources, or the combination of carbon sources, nickel sources, selenium sources and tellurium sources, the proportions of the corresponding combination components, and the preparation conditions such as the processing control temperature may be different.
[0053] Exemplarily, the method for preparing NiSeTe material may be:
[0054] Example 1
[0055] 800 mg of polyacrylonitrile and 700 mg of nickel nitrate hexahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0056] Mix 306 mg of tellurium powder and 191 mg of selenium powder, and grind in a mortar until uniform to obtain a mixture B;
[0057] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0058] The mixture C was placed in a tube furnace and kept at 800°C for 180 min to obtain a NiSeTe material. The morphology of the material is as follows: Figure 1 The particle size of NiSeTe nanoparticles is about 200nm. Figure 1 As shown; the carbon content of the NiSeTe material is 20%.
[0059] like Figure 2 As shown in the figure, according to the calculation results of density functional theory (DFT), the adsorption energy of potassium on the NiSeTe (also known as nickel-based disulfide) surface is -2.35 eV. This low adsorption energy indicates that potassium ions can efficiently migrate from the electrolyte to the electrode surface. Figure 3 It clearly shows that the diffusion barrier energy of potassium ions is only 1.1 eV, and depicts its changes along the reaction path, further confirming that this low barrier is conducive to the rapid ion migration of potassium ions in electrode materials.
[0060] The material prepared in Example 1 was made into electrodes and a potassium ion battery was assembled. Potassium hexafluorophosphate was selected as the electrolyte. The test current density was 0.2 A / g, the capacitance was 400 mAh / g, the charge and discharge cycle was 100 times, and the coulomb efficiency was greater than 96.8%.
[0061] Among them, Coulombic efficiency (CE) is a very important indicator for evaluating the reversibility of battery cycles. Whether the capacity of a battery decays during the cycle and how fast it decays can be qualitatively and quantitatively evaluated by Coulombic efficiency. Due to the development of various battery systems now, the definition of Coulombic efficiency should also be appropriately matched according to different battery systems. With regard to the embodiments of the present disclosure, for the potassium ion battery of the embodiments of the present disclosure, since all active potassium ions come from the positive electrode, the definition of Coulombic efficiency is that during a complete cycle, the amount of potassium ions returning to the positive electrode during the discharge process is greater than the amount of potassium ions escaping from the positive electrode during the charging process. In addition, since a SEI film or other side reactions will be formed on the surface of the negative electrode during the charging process, this will consume a portion of the active potassium ions, resulting in the potassium ions escaping from the positive electrode not being able to completely return to the positive electrode during the subsequent discharge process, so the Coulombic efficiency is less than 100%.
[0062] The higher the coulombic efficiency, the less energy the battery loses during the charging and discharging process, and the higher the battery efficiency and service life.
[0063] Example 2
[0064] 10 mg of graphene and 60 mg of nickel chloride hexahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0065] Mix 26 mg of tellurium powder and 24 mg of selenium powder, and grind in a mortar until uniform to obtain a mixture B;
[0066] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0067] The mixture C is placed in a tube furnace and kept at 850° C. for 120 minutes to obtain a NiSeTe material. The particle size of the NiSeTe nanoparticles is about 600 nm; and the carbon content of the NiSeTe material is 80%.
[0068] The NiSeTe material prepared in this embodiment is assembled into a potassium ion battery, potassium hexafluorophosphate is selected as the electrolyte, the test current density is 0.5A / g, the capacitance value is measured to be 296mAh / g, the charge and discharge cycle is 150 times, and the coulomb efficiency is greater than 98%.
[0069] Example 3
[0070] 50 mg of graphite and 600 mg of nickel acetate tetrahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0071] Mix 412 mg of tellurium powder and 315 mg of selenium powder, and grind in a mortar until uniform to obtain a mixture B;
[0072] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0073] The mixture C is placed in a tube furnace and kept at 850° C. for 60 minutes to obtain a NiSeTe material. The particle size of the NiSeTe nanoparticles is about 600 nm; and the carbon content of the NiSeTe material is 40%.
[0074] The material prepared in this example was used to assemble a potassium ion battery. Potassium hexafluorophosphate was selected as the electrolyte. The test current density was 0.1 A / g. The capacitance was measured to be 510 mAh / g. The coulombic efficiency after 100 charge and discharge cycles was greater than 98.5%.
[0075] Example 4
[0076] 50 mg of graphite and 600 mg of nickel acetate tetrahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0077] Mix 412 mg of tellurium powder and 315 mg of selenium powder, and grind in a mortar until uniform to obtain a mixture B;
[0078] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0079] The mixture C is placed in a tube furnace and kept at 850° C. for 60 minutes to obtain a NiSeTe material. The particle size of the NiSeTe nanoparticles is about 600 nm; and the carbon content of the NiSeTe material is 40%.
[0080] The material prepared in this example was used to assemble a potassium ion battery. Potassium hexafluorophosphate was selected as the electrolyte. The test current density was 0.1 A / g. The capacitance was measured to be 510 mAh / g. The coulombic efficiency after 100 charge and discharge cycles was greater than 98.5%.
[0081] Exemplarily, the method for preparing NiSTe material may be:
[0082] Example 5
[0083] 50 mg of carbon nanotubes and 450 mg of nickel sulfate hexahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0084] Mix 32 mg of sulfur and 309 mg of tellurium powder and grind in a mortar until uniform to obtain mixture B;
[0085] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0086] The mixture C was placed in a container and kept at 1000° C. for 30 minutes to obtain a NiSTe material. The particle size of the NiSTe nanoparticles was about 100 nm; and the carbon content of the NiSTe material was 70%.
[0087] The material prepared in this example was used to assemble a potassium ion battery. Potassium hexafluorophosphate was selected as the electrolyte. The test current density was 0.1 A / g. The capacitance was measured to be 410 mAh / g. The coulombic efficiency after 100 charge and discharge cycles was greater than 98.5%.
[0088] Example 6
[0089] 100 mg of carbon cloth and 600 mg of nickel nitrate hexahydrate were mixed and ground in a mortar until uniform to obtain a mixture A;
[0090] Mix 96 mg of sulfur and 144 mg of tellurium powder and grind in a mortar until uniform to obtain a mixture B;
[0091] Slowly add mixture A into mixture B and stir evenly to obtain mixture C;
[0092] The mixture C is placed in a tube furnace and kept at 900° C. for 30 minutes to obtain a NiSTe material. The particle size of the NiSSe nanoparticles is about 300 nm; and the carbon content of the NiSTe material is 70%.
[0093] The material prepared in this example was used to assemble a potassium ion battery. Potassium hexafluorophosphate was selected as the electrolyte. The test current density was 0.2 A / g. The capacitance was measured to be 300 mAh / g. The coulombic efficiency after 100 charge and discharge cycles was greater than 97.6%.
[0094] In a third aspect, the present disclosure provides a negative electrode plate for a potassium ion battery, wherein the material of the negative electrode plate is the aforementioned nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe. The particle size of the nanoparticles is 100nm-600nm. Specifically, the nickel-based disulfide material also includes a carbon skeleton; the carbon content of the nickel-based disulfide material is 20%-80%.
[0095] The beneficial effects of the embodiments of the present disclosure are the same as those described above and will not be elaborated on herein.
[0096] In a fourth aspect, the present disclosure provides a potassium ion battery, comprising the aforementioned potassium ion battery negative electrode plate.
[0097] The beneficial effects of the embodiments of the present disclosure are the same as those described above and will not be elaborated on herein.
[0098] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the embodiments of the present disclosure. The drawings only show components related to the embodiments of the present disclosure rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0099] The following embodiments of the present disclosure are provided by specific specific examples to illustrate the embodiments of the present disclosure. Those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present disclosure.
[0100] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0101] The embodiments described above are part of the embodiments of the present disclosure, but not all of them. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present disclosure.
[0102] In the description of the embodiments of the present disclosure, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the embodiments of the present disclosure and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present disclosure. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0103] In the description of the embodiments of the present disclosure, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present disclosure can be understood according to specific circumstances.
[0104] The above are only specific implementations of the embodiments of the present disclosure, but the protection scope of the embodiments of the present disclosure is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the embodiments of the present disclosure should be included in the protection scope of the embodiments of the present disclosure. Therefore, the protection scope of the embodiments of the present disclosure should be based on the protection scope of the claims.
Claims
1. A negative electrode material for a potassium ion battery, characterized in that The negative electrode material is a nickel-based disulfide material, the structure of the nickel-based disulfide material is in the form of nanoparticles, and the nickel-based disulfide is one of NiSTe and NiSeTe.
2. The material according to claim 1, characterized in that The particle size of the nanoparticles is 100nm-600nm.
3. The material according to claim 1, characterized in that The nickel-based disulfide material is based on a carbon material, and the carbon material structure includes one or more of a nanotube, a nanowire, a nanosheet, and a porous structure. The carbon content of the nickel-based dichalcogenide material is 20%-80%.
4. A method for preparing the nickel-based dichalcogenide material according to any one of claims 1 to 3, characterized in that: The method includes: Grinding the carbon source and the nickel source uniformly in a first mortar to obtain a mixture A; Grind the sulfur source, one of the selenium source, and the tellurium source uniformly in a second mortar to obtain a mixture B; Add mixture A to mixture B and mix well to obtain mixture C; The mixture C is placed in a heat treatment device for heat treatment to obtain the nickel-based disulfide material. The structure of the nickel-based disulfide material is in the form of nanoparticles. The nickel-based disulfide is one of NiSTe and NiSeTe.
5. The preparation method according to claim 4, characterized in that: The carbon source includes one or more of carbon cloth, carbon nanotubes, carbon nanowires, polyacrylonitrile, graphite, and graphene; The nickel source includes one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel oxalate, and nickel nitrate hexahydrate; The sulfur source includes one or more of thioacetamide, carbon disulfide, sulfur, and thiourea; The selenium source includes selenium powder; The tellurium source includes tellurium powder.
6. The preparation method according to claim 5, characterized in that: The molar ratio of nickel source: carbon source is between 4:1 and 1:9; The molar ratio of the mixture of the sulfur source and the tellurium source, or the mixture of the selenium source and the tellurium source, to the nickel source is 2:
1.
7. The preparation method according to claim 5, characterized in that: The heat treatment device includes a tube furnace.
8. The preparation method according to claim 5, characterized in that: The heating treatment comprises: Keep at 800-1000℃ for 30-180 minutes.
9. A negative electrode plate for a potassium ion battery, characterized in that: The material of the negative electrode plate is the nickel-based disulfide material according to any one of claims 1-8.
10. A potassium ion battery, characterized in that: The potassium ion battery comprises the potassium ion battery negative electrode sheet according to claim 9.